A Facile Method for Preparing Superhydrophobic and Flame‐Retardant Fabrics Materials. Issue 12 (22nd July 2021) - Fang, Zhou; Qin, Yao; He, Yan; Cui, Xue-min
Abstract : Herein, a time‐saving and green method for fabricating superhydrophobic fabrics with excellent hydrophobic and fireproof performances using an alkali‐catalyzed reaction to produce hydrophobic silicone nanofilaments (SNFs) is proposed. Experimental results show that poly‐methylhydrosiloxane (PMHS) can be transformed into SNFs in situ by thermal curing at 120 °C for 30 min under alkaline condition. Adopting this reaction method, the prepared superhydrophobic flexible fabric shows excellent superhydrophobic property with a contact angle of 168°. The oxygen index of the treated fabric is found to increase from 18.77% to 29.40%. Thermogravimetric result shows that the prepared fabric possesses a flame‐retardant property with fire resistance of thermal decomposition temperature of 130 °C. The fabricated fabric has good durability, which maintains superhydrophobicity after being soaked in acid solution (pH = 1) and salt solution (pH = 7) for 36 h. This fabrication process has great potential application for textiles and its composite materials. Abstract : The experiment is dedicated to the preparation of superhydrophobic fabrics with excellent performance by reacting at 120 °C for 30 min and at the same time has durability and fire resistance that is difficult to burn in air. In addition, its mechanism is explained in detail by observing its surface morphology and elemental analysis.